2020
DOI: 10.1002/ejhf.1865
|View full text |Cite
|
Sign up to set email alerts
|

Depression and heart failure: the lonely comorbidity

Abstract: Depression is a frequent and debilitating comorbidity that affects heart failure (HF) patients. Up to 30% of HF patients suffer from depression and even more have depressive symptoms. Moreover, depression carries a risk for HF, especially in high‐risk groups, and is significantly associated with worse quality of life and clinical outcomes. The pathophysiology of depression and HF is poorly understood, but both diseases share several mechanisms and risk factors, including dysregulation of platelet reactivity, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
125
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(132 citation statements)
references
References 122 publications
3
125
2
2
Order By: Relevance
“…Several biological mechanisms have been proposed to explain the worse prognosis of patients with depression and HFrEF, including lifestyle factors, inflammation, autonomic dysfunction, neuroendocrine imbalance and platelet reactivity. The majority of previous studies on depression were conducted in patients with HFrEF, showing that depression is associated with worse clinical status and poor prognosis 35 . Kato et al demonstrated that increased symptoms of depression were associated with an increased risk of adverse cardiac events, independent of HF severity in HFpEF patients 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Several biological mechanisms have been proposed to explain the worse prognosis of patients with depression and HFrEF, including lifestyle factors, inflammation, autonomic dysfunction, neuroendocrine imbalance and platelet reactivity. The majority of previous studies on depression were conducted in patients with HFrEF, showing that depression is associated with worse clinical status and poor prognosis 35 . Kato et al demonstrated that increased symptoms of depression were associated with an increased risk of adverse cardiac events, independent of HF severity in HFpEF patients 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Antidepressants are safe in patients with HF and are not associated with increased mortality. However, there is inadequate evidence that the use of antidepressants effects significant improvement in depression or cardiac outcomes 56,57 Interventions, such as Tai‐Chi, yoga, meditation, relaxation, and stress management may improve quality of life and psychological status 58–60 .…”
Section: Self‐care Behaviour To Maintain Stabilitymentioning
confidence: 99%
“…Moreover, it is well-known that 5-HT is effective not only to treat depression but also to decrease the susceptibility to depression and suicide ( Li and He, 2007 ). Interestingly, stimulation of the serotonergic pathway is thought to be so beneficial that the use of non-pharmacological methods to increase 5-HT levels have been suggested as a potential strategies to prevent depression and/or improve mood and social functioning, by means of exercise ( Sbolli et al, 2020 ) or exposure to bright light ( Harrison et al, 2015 ), for instance.…”
Section: Central 5-ht and Its Role In Systemic Inflammationmentioning
confidence: 99%